2023
DOI: 10.1021/acsanm.2c05482
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Molecular Oxygen Generation via Unexpected Emission Color-Tunable CdSe/ZnS Nanocrystals for Applications in Photodynamic Therapy

Abstract: It is highly desirable in biomedical sciences to utilize the multifunctional nanoparticles of similar size with tunable emission. Since the optoelectronic properties of quantum dots (QDs) originate from size-dependent quantum confinement effects, we developed an alternate approach to synthesize color-tunable CdSe/ZnS QDs based on interfacial ion exchange (predominantly exchange of Se2– by S2– anions), using 1-dodecanethiol and oleylamine solvent systems as a sensitive parameter. The wide-range color-tunability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(52 citation statements)
references
References 75 publications
1
51
0
Order By: Relevance
“…We found different decay values for singlet oxygen in water and chloroform, which were found to be consistent with that for the 1 O 2 previously reported at 3.5 μs (in water) 7 and 215 μs (in chloroform). 5 The observed different lifetimes of 1 O 2 in water and chloroform (Figure 6e,f) were attributed to a different energy transfer from electronic states of 1 O 2 to vibrational states of solvent molecules. The 1 O 2 generation via TET was further confirmed by using α- The 1 O 2 generation is also strongly dependent on the type of doping species, surface chemistry, and concentration of QDs.…”
Section: Development Of Qds-based Sensitizersmentioning
confidence: 95%
See 4 more Smart Citations
“…We found different decay values for singlet oxygen in water and chloroform, which were found to be consistent with that for the 1 O 2 previously reported at 3.5 μs (in water) 7 and 215 μs (in chloroform). 5 The observed different lifetimes of 1 O 2 in water and chloroform (Figure 6e,f) were attributed to a different energy transfer from electronic states of 1 O 2 to vibrational states of solvent molecules. The 1 O 2 generation via TET was further confirmed by using α- The 1 O 2 generation is also strongly dependent on the type of doping species, surface chemistry, and concentration of QDs.…”
Section: Development Of Qds-based Sensitizersmentioning
confidence: 95%
“…The reported studies have revealed that it usually occurs through the triplet energy transfer pathway. 5 Thus, detailed optical properties along with an insight into the electronic structure are paramount to probe the sensitization mechanism of the singlet oxygen generation. X-ray absorption spectroscopy (XAS) is a highly elementspecific technique that probes efficiently the local atomic/ electronic structure of the photoabsorber (metal site) in NCs.…”
Section: Fundamental Optoelectronic Properties Of Qdsmentioning
confidence: 99%
See 3 more Smart Citations